Implications of the Implementation of the New Indonesian Penal Code in 2026 on Legal Certainty and Human Rights - Arianti, Fitri; Noviya, Anis (PT. Hafasy Dwi Nawasena, 2026)
The reform of national criminal law through Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift from a colonial legacy to a codification oriented toward Pancasila values ​​and the protection of human rights. Its full enactment in 2026 raises fundamental questions regarding its implications for legal certainty and the guarantee of citizens' constitutional rights. This study aims to analyze the consistency of the principle of legality, the lex certa principle, and their compliance with human rights standards, including the International Covenant on Civil and Political Rights. The method used is normative legal research with a statutory, conceptual, and analytical-prescriptive approach, through a review of primary and secondary legal materials and grammatical, systematic, and teleological interpretations. The results show that the new Criminal Code normatively strengthens the national codification and integrates more humanistic and restorative criminal goals. However, the expansion of material legality through the recognition of living law in society and the existence of several formulations of crimes with the potential for multiple interpretations poses the risk of legal uncertainty and disproportionate restrictions on rights. Therefore, the success of the Criminal Code reform depends heavily on the consistency of constitutional interpretation, strengthening of due process of law, and the mechanism for testing norms to ensure a balance between legal certainty and the protection of human rights